Clostridium histolyticum (AA4500) for the Treatment of Adhesive Capsulitis of the Shoulder: A Randomised Double-Blind, Placebo-Controlled Study for the Safety and Efficacy of Collagenase – Single Site Report - Fitzpatrick J; Richardson C; Klaber I; Richardson MD (Dove Medical Press, 2020)
Jane Fitzpatrick,1,2 Christen Richardson,3 Ianiv Klaber,4 Martin D Richardson1 1Centre for Health and Exercise Sports Medicine, School of Health Sciences, Faculty of Medicine, Dentistry and Health Sciences, University of Melbourne, Parkville, VIC, Australia; 2Joint Health Institute, Melbourne, VIC, Australia; 3Medical School, College of Health and Medicine, Australian National University, Acton, ACT, Australia; 4Orthopaedic Surgery Department, School of Medicine, Pontifical Catholic University of Chile, Santiago, ChileCorrespondence: Jane FitzpatrickCentre for Health and Exercise Sports Medicine, School of Health Sciences, Faculty of Medicine, Dentistry and Health Sciences, University of Melbourne, Level 7, Allan Gilbert Building, 161 Barry Street, Melbourne, VIC, AustraliaEmail jane.fitzpatrick@unimelb.edu.auBackground/Hypothesis: Adhesive capsulitis of the shoulder results in pain and restricted movement of the glenohumeral joint. Hypothesis: There would be a difference in active range of movement in the affected shoulder of patients with adhesive capsulitis after receiving a series of injections of collagenase Clostridium histolyticum (CCH) compared to placebo.Methods: This study reports the results from a single site that was part of a 321-participant, multicenter, double-blind, prospective parallel-group, randomized controlled clinical trial. Inclusion criteria: over 18 years of age, unilateral idiopathic adhesive capsulitis for > 3 months, but < 12 months. Exclusion criteria: recent physical therapy, injections, subacromial impingement, calcific tendonitis or glenohumeral joint arthritis in the affected shoulder. Subjects were randomized 3:1 to receive CCH 0.58 mg or placebo under ultrasound guidance. Injections were on days 1, 22, and 43. The primary outcome measure was a functional assessment of active range of movement.Results: Overall, 37 patients were screened, 26 subjects were excluded, and 11 subjects were randomly assigned to the treatment group (n=9) or the control group (n=2). Both control and treatment groups showed improvement in ROM between baseline and day 95. In the treatment group, AROM improved from the baseline of 272.89° (SD 86.25) to 462.11° (SD 96.89) and the control group from 246.00° (SD 5.66) to 451.50° (SD 50.20) at day 95 with no statistical difference between groups p=0.78. Site data were in line with the whole study findings. Treatment-related adverse events at the injection site, including haematoma (bruising) and localised pain and swelling, were common.Conclusion: Although the participants showed improvement in function, statistical significance was neither reached in the site nor the overall study cohort. Given the adverse events and the potential risks of the procedure, we would not recommend this drug for the treatment of adhesive capsulitis of the shoulder.Level of Evidence: 2, cohort from one site of RCT.Keywords: adhesive capsulitis, frozen shoulder, collagenase